Penguatan keterampilan mendesain pembelajaran berdiferensiasi terintegrasi kompetensi sosial emosional berbasis website interaktif bagi guru - Teguh Hardi Raharjo; Ahmad Saeroji; Yozi Aulia Rahman; Dea Oktavia; Eko Danu Prasetyo; Ihda Mustofa Ahyaar (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
There are two main aspects of the problems faced by MGMP MPLB teachers in Semarang City that urgently need to be resolved, namely; (1) low conceptual and practical knowledge of teachers related to integrated differentiated learning design for Social Emotional Competence (KSE); and (2) minimal teacher literacy in utilizing digital tools in creating interactive learning websites and Artificial Intelligence as a tool in compiling interactive learning media. The solutions offered to solve these problems are (1) Socialization of the concept of integrated differentiated learning design for KSE; (2) Training in compiling integrated differentiated learning teaching modules for KSE; (3) Training in creating interactive learning websites using Google Sites; (4) Training in creating assignments and educational games along with evaluation instruments using eduaide.ai; (5) Training in creating learning podcasts using Google NotebookLM; (6) Training in creating learning videos using pictory.ai; (7) Training in creating learning comics using comicai.ai. The implementation methods used in this community service program are in the form of socialization, training, and mentoring and evaluation. The main achievements of this program are reflected in the substantial increase in teacher knowledge and skills. The evaluation results showed that there was a significant increase in the average teacher knowledge score from pre-test to post-test, indicating the effectiveness of the comprehensive training method.